GLOBAL IQLIM O‘ZGARIShINING LANDShAFTLARGA TA’SIRI VA ANTROPOGEN OMILLAR - Ochilov, S.Z.; Abdirahmonov, S.T. (SCIENCE and SOCIETY, 2025)
The article analyzes the main impacts of climate change on different landscape types. As a result of factors such as global warming, changes in precipitation and sea level rise, glaciers are melting, desertification is increasing, erosion in coastal areas is increasing, and serious changes are occurring in forests and water resources. The study highlights the impact of these processes on soil, vegetation and water systems, and analyzes threats to ecological balance.
Keywords: climate change; landscape; glaciers; desertification; erosion; sea level; forests; ecosystem